2022
DOI: 10.3389/fonc.2022.850937
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Stage IV Colorectal Cancer Patients With Resection of Liver and/or Pulmonary Metastases: A Population-Based Cohort Study

Abstract: ImportanceCurrently, surgical resection of distant metastatic lesions has become the preferred treatment for select colorectal cancer (CRC) patients with liver metastasis (LM) and/or pulmonary metastasis (PM). Metastasectomy is the most common curative method. However, evidence of the factors affecting the prognosis of CRC patients after resection of LM and/or PM is still insufficient.ObjectiveTo explore the prognostic factors of CRC patients with LM and/or PM who have undergone resection of metastatic tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Integrating radiomics into current prognostic workflows for predicting Ki-67 expression in lung cancer involves incorporating radiomic features extracted from imaging data, such as CT scans, into existing prognostic models. This process requires the development of algorithms that capture intricate patterns related to Ki-67 expression, with subsequent validation against established indicators and clinical outcomes ( 43 , 44 ). Collaboration between radiologists, oncologists, and data scientists is crucial for optimization, standardization, and the establishment of protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating radiomics into current prognostic workflows for predicting Ki-67 expression in lung cancer involves incorporating radiomic features extracted from imaging data, such as CT scans, into existing prognostic models. This process requires the development of algorithms that capture intricate patterns related to Ki-67 expression, with subsequent validation against established indicators and clinical outcomes ( 43 , 44 ). Collaboration between radiologists, oncologists, and data scientists is crucial for optimization, standardization, and the establishment of protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) ranks third in incidence and deaths among men and women as of 2022 [ 25 ]. Considering the substantial burden CRC imposes on the healthcare system, it is imperative to investigate the underlying mechanisms of CRC development to advance novel methods for disease management [ 26 ]. Experiments and analysis conducted by Yimin Li et al [ 24 ] showed that ELFN1-AS1 interacted with DNA methyltransferase 3 alpha (DNMT3a) and enhancer of zeste homolog 2 (EZH2), both of which are involved in histone and DNA methylation processes.…”
Section: Elfn1-as1 Deregulation In Cancermentioning
confidence: 99%
“…The incidence and mortality of colorectal cancer (CRC) have increased significantly in recent years, ranking the 3rd and 5th among all malignant tumors, respectively ( Siegel et al, 2020 ; Zhao et al, 2020 ; Lu et al, 2021 ). Most patients are in the middle and late stages when diagnosed, which seriously threatens the survival and quality of life of patients ( Dekker et al, 2019 ; Cienfuegos-Jimenez et al, 2021 ; Peng et al, 2022 ). The 5-year relative survival ranges from more than 90% in stage I patients to slightly more than 10% in stage IV patients ( Brenner et al, 2014 ; Biswas et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%